Depresión, ideación suicida y consumo de alcohol en estudiantes de Computación de la Universidad Nacional de Loja - León Castillo, María de los Ángeles (2023)
Depression is a determining factor in suicidal behaviour, a risk that increases in people with alcohol consumption problems. The aim of this research was to identify the degree of depression and the presence of suicidal ideation, to assess the type of alcohol consumption according to age group and sex, and to establish their relationship in Computer Science students of the National University of Loja, with a cross-sectional quantitative approach, in a sample of 125 participants, using the self-applied Zung depression scale, the Beck suicidal ideation scale and the alcohol consumption disorders identification test. We found that 79.2% (n=99) were male and 20.8% (n=26) female. Of these, 43.2% (n=54) showed mild depression and 37.6% (n=47) moderate depression, with males predominating with 24.8% (n=31) and 16% (n=20) respectively. Suicidal ideation was reported in 17.6% (n=22); males predominated with 8.8% (n=11). When alcohol consumption was assessed, it was observed that the risk level predominated with 14.4% (n=18), with males standing out with 7.2% (n=9). This was particularly significant in the 20-24 age group. When the variables were related, applying the Chi-square test, with 95% confidence, it was shown that there is a statistically significant association only between depression and suicidal ideation with a value of p=0.0014. Demonstrating that depression may be an important predictor in suicidal thinking and risk